William Blake - Songs of Innocence and of Experience - Sarah Haggarty; Jon Mee (United Kingdom Palgrave Macmillan, 2013)
"Songs of Innocence and of Experience (1794) is William Blake's best-known work, containing such familiar poems as 'London', 'Sick Rose' and 'The Tyger'. Evolving over the author's lifetime, the collection was printed by Blake himself on his own press. This Reader's Guide: * explains the unique development of Songs as an illuminated book * considers the earliest reactions to the text during Blake's lifetime, and his gathering posthumous reputation in the nineteenth century * explores modern critical approaches and recent debates * discusses key topics that have been of abiding interest to critics, including the relationship between text and image in Blake's 'composite art'. Insightful and stimulating, this introductory guide is an invaluable resource for anyone who is seeking to navigate their way through the mass of criticism surrounding Blake's most widely-studied work."
Literary studies: poetry & poets
Undergraduate
Keywords: Literary studies: c 1800 to c 1900; Literary studies: poetry & poets; English